Incorporate competencies in our teaching plan (Journal of Parents and Teachers, 2014)
The elements that define a teaching plan are the general objectives in every stage and every course: developing capacities; basic competencies; contents: concepts, procedures and values; methodology and evaluation criteria. Decomposing the basic competencies in concrete indicators is not easy and requires a way of working. In this article we can find guidelines of how to do it. However, what are the basic competencies? Knowledge, abilities, attitudes, capacities and aptitude adapted to a context that allow people to act efficiently and deal with situations.
Keywords: teachers’ formation; basic competencies; teaching plan; LOE; educative laws